Rights and Duties of Husband and Wife in the Perspective of Prophetic Hadiths in the Book of 'Uqūd Al-Lujayn: A Study of Hadith Syarah - Ina Alif Hamdalah; Shabrun Jamil (Jurnal Riset Agama, 2022)
The rights and obligations of husband and wife are very important things in marriage. This research aims to discuss problem the rights and obligations of husband and wife in the perspective of hadith the prophet in the book of ‘Uqūd al-Lujayn, by comparing various sharah hadith. The type of research is qualitative research using library studie, by method sharah muqaran (comparative) from the book mashadir ashliyah to explain central themes in the hadith. The results of this study show that the book ‘Uqūd al-Lujayn the husband and wife have rights and obligations that is, husband should lead his family and has to treat his wife well. Wife also has the right to receive a living from her husband and the wife has to obedient the husband. Conclusion from research is there are several hadith that explain the right and obligation of the husband and wife, Shahih Bukhari No. 2751, Sunan Tirmidzi No. 1163, Musnad Ahmad No. 19162, Musnad Ahmad No. 1573.